2022
DOI: 10.3389/fenvs.2022.1013657
|View full text |Cite
|
Sign up to set email alerts
|

WASH facilities prevalence and determinants: Evidence from 42 developing countries

Abstract: Improved WASH facilities are crucial for reducing infectious diseases such as diarrhoea, malaria, dengue, and worms, etc. However, a large proportion of households in developing countries lack basic WASH facilities. Therefore, the current paper uses the household data from 733,223 households in fourty two developing countries to explore the prevalence rate of basic WASH facilities. The result shows that access to basic drinking water is much better than access to other WASH facilities, such as basic sanitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A study on WASH facilities prevalence and determinants from 42 developing countries indicated that only about 64% of the households had access to basic water, which places countries such as Chad and Ethiopia at the receiving end (Rahut et al, 2022). This poses a massive threat to the life of children as they are more exposed to waterborne diseases such as cholera (Charnley et al, 2022).…”
Section: Inequalities In Infectious Diseases and Wash Programsmentioning
confidence: 99%
“…A study on WASH facilities prevalence and determinants from 42 developing countries indicated that only about 64% of the households had access to basic water, which places countries such as Chad and Ethiopia at the receiving end (Rahut et al, 2022). This poses a massive threat to the life of children as they are more exposed to waterborne diseases such as cholera (Charnley et al, 2022).…”
Section: Inequalities In Infectious Diseases and Wash Programsmentioning
confidence: 99%
“…Unfortunately, there are vast gaps in the implementation and management of WASH facilities such as health station handwashing areas and waste systems in a health care structure (Potgieter et al, 2021). However, there are gaps in the implementation and management of WASH facilities, such as handwashing stations and waste systems, in many healthcare facilities (Rahut et al, 2022;Sridhar et al, 2020). Additionally, the prevalence of basic WASH facilities varies across different regions and countries, with lower access in Africa and South Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Improved water, sanitation, and hygiene (WASH) practices are crucial for public health (Cumming et al, 2019;Meadors et al, n.d.;Rahut et al, 2022;Shrestha et al, 2022;Traoré et al, 2023). Access to adequate WASH services, including clean drinking water, sanitation facilities, and handwashing with soap, is essential for preventing infectious diseases such as diarrhea, respiratory illnesses, and typhoid fever.…”
Section: Introductionmentioning
confidence: 99%